2018
DOI: 10.1093/annonc/mdy123
|View full text |Cite|
|
Sign up to set email alerts
|

Early evolutionary divergence between papillary and anaplastic thyroid cancers

Abstract: ATC diverge from PTC early in tumour development and both tumour types evolve independently. Our work allows the understanding of the relationship between ATC and PTC facilitating the clinical management of these malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…Additionally, many ATCs carry mutations, such as BRAF Val600Glu or NRAS Gln61Arg, that are signature mutations of WDTCs. A recent publication including 3 ATC/PTC pairs, however, challenged this school of thought by showing few shared mutations at high VAF and concluded that ATCs and WDTCs were likely evolutionarily largely independent . Our study explores this question in a relatively larger cohort and investigates the hypothesis more extensively through clonality‐based evolutionary analysis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, many ATCs carry mutations, such as BRAF Val600Glu or NRAS Gln61Arg, that are signature mutations of WDTCs. A recent publication including 3 ATC/PTC pairs, however, challenged this school of thought by showing few shared mutations at high VAF and concluded that ATCs and WDTCs were likely evolutionarily largely independent . Our study explores this question in a relatively larger cohort and investigates the hypothesis more extensively through clonality‐based evolutionary analysis.…”
Section: Discussionsupporting
confidence: 94%
“…Although the coexistence of well‐differentiated and anaplastic tumors and their partly overlapping genetic profiles are suggestive of a genetic pathway of dedifferentiation of ATC from a well‐differentiated tumor, this hypothesized progression has not been extensively investigated with next‐generation sequencing approaches. A recent study of 3 paired ATCs and papillary thyroid carcinoma (PTCs) suggested early divergence of ATC and PTC and concluded that they were largely distinct entities . However, that study's small sample size and exclusion of follicular thyroid carcinomas (FTCs) restricts the generalizability of the conclusions, and methodological assumptions may obscure the overlapping mutational profiles of the 2 tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Anaplastic thyroid cancer (ATC), accounting for 1-5% of all thyroid malignancies, is one of the most malignant endocrine tumors, with a patient median survival of less than 1 year [1]. ATC may arise de novo or by dedifferentiation of pre-existing well-differentiated thyroid tumors [2,3]. Deciphering its pathogenesis is likely to lead to the development of more effective therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent improvements in treating PTC, for example surgery, radioiodine and endocrine therapy. PTC cells still showed occasional metastasis, loss of differentiation, anaplastic thyroid and high aggressiveness [4,5]. Hence, the elucidation of mechanism and novel targets of signaling involved in PTC oncogenesis are still required.…”
Section: Introductionmentioning
confidence: 99%